Strengthening Digital Citizens Political Communication Ethics (Digital Citizenship) in Social Media - Dwiputra, Rahyudi; Aziz, Thoriq Abdul; Nur, Muhammad (International Journal Pedagogy of Social Studies, 2022)
Social media as a communication channel is an important target of political socialization. Social media's breadth of reach and depth of influence is a hunt for political communicators to convey their messages and political campaigns. However, ethics is not used as the main basis in conveying messages and political campaigns on social media in practice. This research aims to find out how to strengthen the ethics of political communication in social media. The research method used is a literature study or literature review study. The results of this paper indicate that for political communicators, communication ethics must be the main basis for conveying political messages and campaigns on social media. In addition, the public must become digital citizens who are good at reading the communication patterns of political actors on social media so that they are not trapped by hoaxes and contain elements of the division.